Phenolic Profile and Antioxidant Activity of Italian Monovarietal Extra Virgin Olive Oils - Carmine Negro; Alessio Aprile; Andrea Luvisi; Francesca Nicolì; Eliana Nutricati; Marzia Vergine; Antonio Miceli; Federica Blando; Erika Sabella; Luigi De Bellis (MDPI AG, 2019)
In the last years, the interest in Italian monovarietal oils has increased due to their specific organoleptic qualities. Extra virgin olive oils (EVOOs) are rich in phenolic compounds, secondary metabolites well known and studied for their nutraceutical properties. However, among EVOOs, there is great variability in phenolic composition due to the origin, the production technique, and mainly, the genotype. The aim of this work was to evaluate the different phenolic profiles and the antioxidant activities of monovarietal oils. The results confirm this variability. In fact, the overall content of oleuropein varies up to four times between the different genotypes (from 33.80 to 152.32 mg/kg oil), while the oleocanthal content is significant only in two oils. The antioxidant activity, determined with 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and oxygen radical absorbance capacity (ORAC) assays, is correlated with the content of total phenolic substances, with half maximal inhibitory concentration (IC50) values for the DPPH test ranging from 160 to 91 mg of oil, while the ORAC test shows values between 5.45 and 8.03 μmol Trolox equivalent (TE)/g oil.